A method for preparing polyacrylamide nanocomposite hydrogel using magnetic field orientation

Preparation of polyacrylamide nanocomposite hydrogels through magnetic field orientation method solves the problem of poor mechanical strength of traditional hydrogels, achieves the formation of anisotropic structures and improves mechanical properties, and provides high-performance materials for bioengineering and other fields .

CN115594868BActive Publication Date: 2025-01-14UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211406936.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2025-01-14
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

Traditional hydrogel networks are disorderly oriented, soft and have poor mechanical strength, limiting their widespread use in bioengineering applications.

Method used

Polyacrylamide nanocomposite hydrogels were prepared by magnetic field orientation method, and anisotropic hydrogels were formed by depositing Fe3O4 nanoparticles on the surface of diatomaceous earth and guiding their arrangement under the action of magnetic field.

Benefits of technology

Improves the mechanical properties and directionality of hydrogels and provides high-performance materials for soft tissue engineering and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115594868B_ABST
    Figure CN115594868B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation, including two steps of preparing PDA-Fe3O4-SiO2 paramagnetic nanocomposite and preparing oriented hydrogel; the preparation method of oriented hydrogel is as follows: dispersing PDA-Fe3O4-SiO2 paramagnetic nanocomposite in polydopamine solution, ultrasonicating, forming ferrofluid; then adding acrylamide monomer, initiator, crosslinking agent and catalyst, stirring at room temperature, forming a uniform gel precursor solution; finally, pouring the gel precursor solution into a silica gel mold, putting it into a magnetic field, and forming oriented hydrogel under magnetic field conditions. The invention improves the directionality of the hydrogel microstructure by introducing magnetic nanocomposite into the gel, and the prepared oriented hydrogel has an anisotropic hydrogel with prominent anisotropic structure and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel preparation, and in particular relates to a method for preparing polyacrylamide nanocomposite hydrogel by utilizing magnetic field orientation. Background Art

[0002] As we all know, hydrogel is a substance similar to biological soft tissue. Its classic three-dimensional cross-linked polymer network structure allows it to maintain the dual properties of solid and liquid. Its excellent flexibility, biocompatibility and good chemical stability make it one of the best candidate materials for bioengineering applications. However, compared with highly ordered biological tissues, traditional hydrogel networks are disordered, soft and weak, which seriously limits its application.

[0003] In order to expand the application of traditional hydrogels, researchers have studied various methods for making oriented hydrogels, including magnetic field induction, electric field induction, mechanical pre-stretching and oriented freezing. Magnetic nanoparticles have become a potential material for preparing anisotropic hydrogels due to their advantages such as fast response speed and high controllability.

[0004] The contact method for making oriented hydrogel is simple to operate and has strong practicality, but the oriented structure of the gel is highly dependent on external forces and is easily affected by other factors. In order to solve this problem, the present invention adopts a non-contact method for making oriented hydrogel. Under the action of an external magnetic field, dipole interactions are generated between magnetic nanoparticles, providing sufficient power for the rapid assembly of anisotropic hydrogels. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing polyacrylamide nanocomposite hydrogel using magnetic field orientation to solve the problem of poor mechanical strength of polyacrylamide hydrogel and to provide an anisotropic polyacrylamide nanocomposite hydrogel.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions:

[0007] A method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation comprises the following steps:

[0008] Preparation of PDA-Fe3O4-SiO2 paramagnetic nanocomposites:

[0009] Dissolve dopamine hydrochloride in deionized water, then add diatomaceous earth, stir and mix at room temperature, so that dopamine is coated on the surface of diatomaceous earth to form a dopamine-diatomaceous earth dispersion system;

[0010] Add FeCl2·4H2O and FeCl3·6H2O into the above dispersion system at a molar ratio of 1:2 and mix well; heat to 80-100°C, drop alkali solution into the solution to make the pH value of the solution ≥10, stir at room temperature to precipitate;

[0011] The precipitate was centrifuged, washed with deionized water until neutral, and then freeze-dried to obtain a PDA-Fe3O4-SiO2 paramagnetic nanocomposite.

[0012] Preparation of oriented hydrogels:

[0013] The paramagnetic nanocomposite is dispersed in a polydopamine solution and subjected to ultrasound to form a ferrofluid;

[0014] Adding acrylamide monomer, initiator, crosslinking agent and catalyst into the ferrofluid and stirring at room temperature to form a uniform gel precursor solution;

[0015] The gel precursor solution was poured into a silicone mold and placed in a magnetic field for 1-5 h, and then the magnetic field was removed to continue the polymerization reaction to form a polyacrylamide nanocomposite hydrogel.

[0016] Furthermore, the alkaline solution is at least one of a NaOH solution and a KOH solution, and the concentration is 1-2 mol / L; after the alkaline solution is dripped in, the pH is adjusted to 12.

[0017] Furthermore, the initiator is ammonium persulfate, the cross-linking agent is N,N-methylenebisacrylamide, and the catalyst is tetramethylethylenediamine.

[0018] Furthermore, the mass ratio of the acrylamide monomer, initiator, crosslinking agent and catalyst added is 4:(0.005-0.015):(0.005-0.015):(0.01-0.02).

[0019] Furthermore, the polydopamine solution is an aqueous solution with a concentration of 1 mg / ml.

[0020] Furthermore, the weight-to-volume ratio of the added paramagnetic nanocomposite to the polydopamine solution is (0.5-2):1000.

[0021] Furthermore, the weight-to-volume ratio of the added acrylamide monomer to the ferromagnetic fluid is (1-3):10.

[0022] Furthermore, the weight-to-volume ratio of the added dopamine hydrochloride to deionized water is (0.2-0.4):20; the weight ratio of the added dopamine hydrochloride to diatomaceous earth is (2-4):20.

[0023] Furthermore, the amount of FeCl2·4H2O added is the same as the amount of diatomaceous earth added.

[0024] Furthermore, in step S6, the magnetic field conditions added are:

[0025] The test was carried out at room temperature, using a parallel magnetic field and two rectangular strong neodymium magnets, 100 mm long, 5 mm wide and 10 mm high; the distance between the two magnets was 4 cm.

[0026] In the present invention, dopamine molecules are first fixed on the diatomite surface by II-II stacking interactions, thereby forming active sites on the diatomite surface. Then, dopamine molecules and ferrous ions are chelated, and due to the powerful metal ion chelating ability of catechol groups, catechol iron precursors are formed. Under alkaline conditions, magnetic nanocomposites are grown in situ with catechol iron precursors as crystal nuclei. At the same time, dopamine undergoes self-polymerization, which limits the diffusion of iron ions.

[0027] The polymerization reaction of acrylamide conforms to the general rules of free radical chain polymerization. Free radical polymerization is generally divided into basic reaction units such as chain initiation, chain growth, and chain termination, and is also accompanied by chain transfer reactions.

[0028] Subsequently, during the polymer formation process, intramolecular and intermolecular hydrogen bonds are formed in part of the PAM chain, and a microcrystalline structure is formed between the PAM molecules as a physical crosslinking point to form a gel. Along the orientation direction, the hydroxyl groups on the surface of the PDA-Fe3O4-SiO2 nanocomposite interact with the polymer chains to form hydrogen bonds, that is, an anisotropic hydrogel is formed. As the gel is formed, the ordered structure is fixed in the hydrogel, marking the acquisition of anisotropic hydrogels.

[0029] Beneficial effects of the present invention:

[0030] (1) The present invention has developed a method for preparing nanocomposite hydrogels using magnetic field orientation. Fe3O4 nanoparticles are deposited in situ on the surface of diatomaceous earth by mediated precipitation to obtain a nanocomposite with paramagnetic properties. The magnetic field-induced orientation strategy is then used to arrange the magnetic nanocomposite in a forward direction in the gel network. Finally, the oriented hydrogel is formed by in situ polymerization.

[0031] (2) The prepared polyacrylamide nanocomposite hydrogel introduces magnetic nanocomposites into the gel to improve the directionality of the hydrogel microstructure, and has outstanding anisotropy and excellent mechanical properties; this invention provides the possibility for designing new high-performance materials for application in soft tissue engineering, soft mechanical engineering and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1a) is a schematic diagram of the structure of dopamine and diatomaceous earth, b) is a schematic diagram of the structure of diatomaceous earth-polydopamine nanocomposite material, and c) is a schematic diagram of the structure of Fe3O4 growing on the surface of the nanocomposite material.

[0033] Figure 2 Schematic diagram of the polymerization mechanism of acrylamide.

[0034] Figure 3 Schematic diagram of the interaction between PAM polymer chains and magnetic nanomaterials.

[0035] Figure 4 Infrared spectrum of the PDA-Fe3O4-SiO2 paramagnetic nanocomposite prepared in Example 1.

[0036] Figure 5 This is a diagram showing the preparation effect of magnetic nanocomposite ferrofluid.

[0037] Figure 6 This is a microscope image of the isotropic hydrogel prepared in Comparative Example 1.

[0038] Figure 7 This is a microscope image of the anisotropic hydrogel prepared in Example 1.

[0039] Figure 8 Graphs showing typical tensile stress-strain curves of the anisotropic hydrogels of Example 1 and the isotropic hydrogels of Comparative Example 1. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited to these embodiments.

[0041] Embodiment 1:

[0042] 1. First, dissolve 0.3 g of dopamine hydrochloride in 20 ml of deionized water, then add 2 g of diatomaceous earth to disperse it in the dopamine solution, stir at room temperature for 0.5 h to coat the dopamine on the surface of the diatomaceous earth to form a dopamine-diatomaceous earth dispersion system.

[0043] 2. Add 2g FeCl2·4H2O and 5.2g FeCl3·6H2O to the above dispersion system and stir at room temperature for 0.5h; raise the temperature to 90℃, drop 1.5mol / L NaOH solution to make the solution pH = 12, stir at room temperature for 2h to precipitate.

[0044] 3. Collect the produced magnetic nanocomposites, centrifuge at 8000 r / min for 5 minutes, wash with deionized water until neutral, and then freeze-dry to obtain PDA-Fe3O4-SiO2 paramagnetic nanocomposites.

[0045] 4. Disperse 0.02 g of paramagnetic nanocomplex in 20 ml of 1 mg / ml polydopamine aqueous solution and ultrasonicate for 5 min to form a ferrofluid.

[0046] 5. Add 4 g acrylamide monomer, 0.01 g initiator (ammonium persulfate), 0.01 g cross-linking agent (N,N-methylenebisacrylamide) and 20 μL catalyst (tetramethylethylenediamine) to 20 ml ferrofluid and stir at room temperature for 10 min to form a uniform gel precursor solution.

[0047] 6. Pour the gel precursor solution into a silicone mold, place it in a magnetic field for 3 hours, orient it under the magnetic field conditions, then remove the magnetic field and continue the polymerization reaction for 24 hours to form a polyacrylamide nanocomposite hydrogel.

[0048] Embodiment 2:

[0049] 1. First, dissolve 0.4 g of dopamine hydrochloride in 20 ml of deionized water, then add 4 g of diatomaceous earth to disperse it in the dopamine solution, stir at room temperature for 0.5 h to coat the dopamine on the surface of the diatomaceous earth to form a dopamine-diatomaceous earth dispersion system.

[0050] 2. Add 4g FeCl2·4H2O and 10.4g FeCl3·6H2O to the above dispersion system and stir at room temperature for 0.5h; raise the temperature to 80℃, drop 2mol / L KOH solution to make the solution pH = 11, stir at room temperature for 1.5h to precipitate.

[0051] 3. Collect the produced magnetic nanocomposites, centrifuge at 8000 r / min for 5 minutes, wash with deionized water until neutral, and then freeze-dry to obtain PDA-Fe3O4-SiO2 paramagnetic nanocomposites.

[0052] 4. Disperse 0.04 g of paramagnetic nanocomplex in 20 ml of 1 mg / ml polydopamine aqueous solution and ultrasonicate for 5 min to form a ferrofluid.

[0053] 5. Add 6 g acrylamide monomer, 0.02 g initiator (ammonium persulfate), 0.02 g cross-linking agent (N,N-methylenebisacrylamide) and 38 μL catalyst (tetramethylethylenediamine) to 20 ml ferrofluid and stir at room temperature for 10 min to form a uniform gel precursor solution.

[0054] 6. Pour the gel precursor solution into a silicone mold, place it in a magnetic field for 5 hours, orient it under the magnetic field conditions, then remove the magnetic field and continue the polymerization reaction for 20 hours to form a polyacrylamide nanocomposite hydrogel.

[0055] Embodiment 3:

[0056] 1. First, dissolve 0.2 g of dopamine hydrochloride in 20 ml of deionized water, then add 1 g of diatomaceous earth to disperse it in the dopamine solution, stir at room temperature for 0.5 h to coat the dopamine on the surface of the diatomaceous earth to form a dopamine-diatomaceous earth dispersion system.

[0057] 2. Add 1g FeCl2·4H2O and 2.6g FeCl3·6H2O to the above dispersion system and stir at room temperature for 0.5h; raise the temperature to 100℃, drop 1mol / L NaOH solution to make the solution pH=10, stir at room temperature for 2h to precipitate.

[0058] 3. Collect the produced magnetic nanocomposites, centrifuge at 8000 r / min for 5 minutes, wash with deionized water until neutral, and then freeze-dry to obtain PDA-Fe3O4-SiO2 paramagnetic nanocomposites.

[0059] 4. Disperse 0.01 g of paramagnetic nanocomplex in 20 ml of 1 mg / ml polydopamine aqueous solution and ultrasonicate for 5 min to form a ferrofluid.

[0060] 5. Add 2 g acrylamide monomer, 0.003 g initiator (ammonium persulfate), 0.003 g cross-linker (N,N-methylenebisacrylamide) and 8 μL catalyst (tetramethylethylenediamine) to 20 ml ferrofluid and stir at room temperature for 10 min to form a uniform gel precursor solution.

[0061] 6. Pour the gel precursor solution into a silicone mold, place it in a magnetic field for 1 hour, orient it under the magnetic field conditions, then remove the magnetic field and continue the polymerization reaction for 28 hours to form a polyacrylamide nanocomposite hydrogel.

[0062] The magnetic field conditions used in Examples 1-3 are:

[0063] The test was carried out at room temperature, and the magnetic field used was a parallel magnetic field, that is, a magnetic field created by two rectangular (100 mm long, 5 mm wide, 10 mm high) strong neodymium magnets (brand N35), the two magnets were 4 cm apart, and the silicone mold was placed in the middle of the two magnets.

[0064] Comparative Example 1

[0065] The preparation method of polyacrylamide nanocomposite hydrogel is the same as that of Example 1, except that in step 6, no magnetic field is placed, and the hydrogel is not oriented under magnetic field conditions.

[0066] Comparative Example 2

[0067] A method for preparing a Fe3O4 nanosheet cross-linked polyacrylamide hydrogel comprises the following steps:

[0068] (1) Weigh 1.09 g of ferric chloride hexahydrate, add 2.8 mL of ultrapure water, 40 mL of anhydrous ethanol, and 5.0 g of anhydrous sodium acetate, transfer the mixture to a 100 mL stainless steel hydrothermal kettle, heat to 170°C for reaction for 12 h, and then separate and wash. Add 100 mL of ultrapure water and 5 mL of polyacrylic acid aqueous solution (MW=1800, 7.2 mg / mL), stir with a magnetic stirrer for 24 h, then centrifuge and wash, and disperse in 60 mL of ultrapure water (about 5 mg / mL).

[0069] (2) Take 100 mg of Fe2O3 nanosheets, add 12 mL of ultrapure water, 80 mL of anhydrous ethanol, 4 mL of ammonia water, and 250 μL of tetraethyl orthosilicate, react at room temperature for 30 min, and wash with ethanol by centrifugation.

[0070] (3) Take the above Fe2O3 / SiO2 nanosheets, add 60 mL of tetraethylene glycol, react at 320°C for 4 h under nitrogen protection, and wash with ethanol by centrifugation to obtain Fe3O4 / SiO2 nanosheets.

[0071] (4) Ultrapure water was added to make the concentration of the Fe3O4 / SiO2 nanosheet aqueous solution 20 mg / mL, and an external magnetic field strength of 50 mT was applied for a magnetic field action time of 5 s to obtain a cross-linked structure of the Fe3O4 nanosheet.

[0072] (5) 80 mg of the above nanosheets were dispersed in 2 mL of ethylene glycol, 0.50 g of acrylamide, 6 mg of N,N'-methylenebisacrylamide, and 6 mg of 2,2-ethoxyacetophenone were added, and stirred for 20 min. Under 285 nm ultraviolet light irradiation, an external magnetic field strength of 50 mT was applied, and the reaction time was 15 min to obtain a polyacrylamide hydrogel based on the cross-linked structure of Fe3O4 nanosheets.

[0073] Comparative Example 3

[0074] (1) 0.02 g of Fe3O4 / SiO2 nanosheets (prepared by the method of Comparative Example 2) were dispersed in 20 ml of a 1 mg / ml polydopamine aqueous solution and ultrasonicated for 5 min.

[0075] (2) Add 4 g of acrylamide monomer, 0.01 g of initiator (ammonium persulfate), 0.01 g of crosslinker (N,N-methylenebisacrylamide) and 20 μL of catalyst (tetramethylethylenediamine) to 20 ml of the above solution and stir at room temperature for 10 min to form a uniform gel precursor solution.

[0076] (3) The gel precursor solution was poured into a silicone mold, placed in a magnetic field for 3 h, and then the magnetic field was removed, and the polymerization reaction was continued for 24 h to form a polyacrylamide nanocomposite hydrogel.

[0077] Comparative Example 4

[0078] The preparation method of polyacrylamide nanocomposite hydrogel is the same as that of Example 1, except that in step 2, FeCl2·4H2O is not added, but only 5.2 g FeCl3·6H2O is added; and in step 3, PDA-Fe2O3-SiO2 nanocomposite is obtained.

[0079] The mechanical properties of the polyacrylamide nanocomposite hydrogel prepared by the present invention and the hydrogel prepared by the comparative example were tested. The test results are shown in Table 1.

[0080] Table 1 Mechanical properties test data of hydrogels prepared in Examples and Comparative Examples

[0081]

[0082] From the above table, it can be seen that in Example 1, from the strain point of view, the mechanical strain in the parallel direction is 820%, which is twice that in the vertical direction; from the force point of view, the fracture stress in the parallel direction is 0.149MPa, which is 2.8 times that in the vertical direction; from the toughness analysis, the toughness in the parallel direction is 68.78KJ / m 3 , the toughness in the vertical direction is 12.69KJ / m 3 The difference between the two is 5.42 times. The mechanical strain of the unoriented hydrogel (Comparative Example 1) is only 550%, the fracture stress is 0.07MPa, and the toughness is 26.21KJ / m 3 , the mechanical properties are not as good as those of oriented hydrogels.

[0083] In the present application, the weight in the “weight to volume ratio” is compared in “g” and the volume is compared in “ml”.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing polyacrylamide nanocomposite hydrogel using magnetic field orientation, characterized in that: The following steps are involved: S1: dissolving dopamine hydrochloride in deionized water, then adding diatomaceous earth, stirring and mixing at room temperature, so that dopamine is coated on the surface of the diatomaceous earth to form a dopamine-diatomaceous earth dispersion system; S2: Add FeCl2·4H2O and FeCl3·6H2O into the above dispersion system at a molar ratio of 1:2 and mix well; heat to 80-100°C, drop alkaline solution into the solution to make the pH value of the solution ≥10, stir at room temperature to precipitate; S3: centrifuging the above precipitate, washing it with deionized water until it is neutral, and then freeze-drying it to obtain a PDA-Fe3O4-SiO2 paramagnetic nanocomposite; S4: dispersing the paramagnetic nanocomposite in a polydopamine solution, and performing ultrasound to form a ferrofluid; S5: adding acrylamide monomer, initiator, crosslinking agent and catalyst into the ferrofluid, stirring at room temperature to form a uniform gel precursor solution; S6: pouring the gel precursor solution into a silicone mold, placing it in a magnetic field for 1-5 hours, then removing the magnetic field to continue the polymerization reaction to form a polyacrylamide nanocomposite hydrogel; The initiator is ammonium persulfate, the cross-linking agent is N,N-methylenebisacrylamide, and the catalyst is tetramethylethylenediamine.

2. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: The alkaline solution is at least one of a NaOH solution and a KOH solution, and the concentration is 1-2 mol / L.

3. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: Step S2: After adding the alkaline solution dropwise, adjust the pH to 12.

4. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: The mass ratio of the acrylamide monomer, initiator, crosslinking agent and catalyst added is 4: (0.005-0.015): (0.005-0.015): (0.01-0.02).

5. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: The polydopamine solution in step S4 is an aqueous solution with a concentration of 1 mg / ml.

6. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: In step S4, the weight to volume ratio of the added paramagnetic nanocomposite to the polydopamine solution is (0.5-2):1000.

7. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: In step S5, the weight-to-volume ratio of the added acrylamide monomer to the ferromagnetic fluid is (1-3):

10.

8. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: In step S1, the weight to volume ratio of the added dopamine hydrochloride to deionized water is (0.2-0.4):20; the weight ratio of the added dopamine hydrochloride to diatomaceous earth is (2-4):20; in step S2, the amount of FeCl2·4H2O added is the same as the amount of diatomaceous earth added in step S1.

9. The method for preparing polyacrylamide nanocomposite hydrogel by magnetic field orientation according to claim 1, characterized in that: In step S6, the magnetic field conditions added are: The test was carried out at room temperature, using a parallel magnetic field and two rectangular strong neodymium magnets, 100 mm long, 5 mm wide and 10 mm high; the distance between the two magnets was 4 cm.

Citation Information

Patent Citations

  • Dopamine modified diatomite heavy metal adsorption hydrogel and preparation method and application thereof

    CN112646095A

  • Preparation method of multi-response anisotropic magnetic hydrogel

    CN112876598A